Juventude e violência na compreensão de jovens : um estudo de representações sociais - Cruz, Suzyelaine Tamarindo Marques da (2016)
This study sought to comprehend the social representations of violence and their relationships with youth for young people. Two instruments were used for data collection: a questionnaire composed by free association as well as sociodemographic questions; and a semi-structured interview model. 308 young university students answered to the first instrument and 14 answered to the latter. The participants were approached in institutions of higher education located in Vitoria/ES. The representation of young people was anchored by the traditional perception of youth. Youth was characterized as a period of preparation for the future in which young people have a certain freedom to do almost everything they desire, as long as their obligations are not denied. The testimonies express and objectify a young person that commits violence in the figure of a black boy who lives in a slum area, matching the stereotype of criminals featured in the news. The prevention strategies identified were directed to young people of low income class. Investing in educational quality was the main strategy cited to avert young people from engaging in paths that lead to violence.